MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA TUNRUNGU KELAS 6 DI SDLB-B - Rahmadana, Dinar (Jurnal Pendidikan Khusus, 2016)
Abstract The purpose of this research was to know whether there was influence of inquiry learning model toward thinking critic ability to the sixth class of hearing impairment students in SDLB-B Karya Mulia Surabaya. Hearing impairment made the speech and language development of hearing impairment children hindered. Speech and thinking ability influenced each other between one to another so that it influenced toward cognitive ability of the hearing impairment children, one of them was thinking critic ability, and caused knowledge competition emphasizing to hearing impairment children’s comprehension about the cause of thing change (putrefaction, corrosion, and weathering) very low. Therefore, to solve the problem required effective learning model and it was adapted to the characteristics and needs of hearing impairment children. One of the things which could be used to develop thinking critic ability of hearing impairment students was by applying inquiry learning model in learning process. The method used was quantitative approach with pre-experiment design arrangement and the design was One-Group Pretest-posttest. The sample was the sixth class students of SDLB Karya Mulia I Surabaya numbering 6 people. The data collection technique used test, observation, and documentation. The suitable instruments used in this research consisted of pretest and posttest exercises. The data of pretest and posttest result was then analyzed using statistic non parametric with quantitative data and the total sample was less than 30 i.e. n = 6. The data of pretest and posttest result was then analyzed using statistic non parametric i.e. sign test formula. The research result indicated that the result of pretest average value was 35,6 and the average value of posttest was 82,8. The result of data analysis indicated that the value of Z counted was 2,05 and Z table was 1,96 with the critic value α = 5%, so it could be concluded that Ho was refused and Ha was accepted, it meant that there was influence of inquiry learning model toward thinking critic ability to the sixth class of hearing impairment students in SDLB-B Karya Mulia I Surabaya.   Keywords: Inquiry learning model, thinking critic ability